A study on bulk terminal operations and facilities at Port Klang / Nor Zuhrah Mustafa - Mustafa, Nor Zuhrah (1994)
One major hypothesis was outlined in search for the answers for the Bulk Terminal's handling operations. Among the answers are the narrow quay at the bulk wharves for lorry movements or marshalling, limited storage space, inefficient conveyor system and cranes breakdown problems.